Estética marxiana e formação humana : inspirações para a educação física escolar e inclusão - Siquara, Zelinda Orlandi (2015)
This paper aims to add to the enrichment of the educational criticism theory, especially regarding to an inclusive Physical Education in schools, from possible inspirations of the Marxism treatment in the human aesthetic dimension. That way, it consists in a theoretical study based on the Marxist theory, specifically on the writings of Karl Marx. For the study broke of three hypotheses that over work is consolidated as discussion points: a) Discussing the human formation from the Marxist aesthetics; b) Physical education: inspiration from the aesthetic knowledge and Marxian; c) Inspirations of Marxist aesthetics to reframe the role of schools and the inclusion processes. The first axis Discussing human development from the Marxist aesthetics, the framework helped us to identify the concept of Marxist aesthetics, education of social meanings for full training is an important element to be glimpsed a guy develop, and also that it is the presence of the other that the subject is constituted. In the second axis, Physical Education: inspiration from Marxist aesthetic knowledge, reinforce that physical education has its specific focus on body, one produced aesthetic knowledge and appropriated by the body, and its importance for an enlarged training. Physical Education wins thus notoriety in the school context. The third axis, Inspirations of Marxist aesthetics to reframe the role of schools and the inclusion process, we identified that the school is one of the social spaces of great importance to the process of becoming human. Finally, the school is in its democratic essence, it is the locus of diversity. Accommodating diversity in becoming human and socialize the diversity of knowledge is its maximum.